2020
DOI: 10.1016/j.cortex.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The role of interoception in understanding others' affect. Dissociation between superficial and detailed appraisal of facial expressions

Abstract: Embodied models of social cognition argue that others' emotional states are processed by re-enacting a representation of the same state in the observer, along with associated somatic and physiological responses. In this framework, previous studies tested whether a strong sensitivity to interoceptive signals (i.e., inputs arising from within one's body) facilitates the understanding of others' affect, leading to mixed results. Such heterogeneity in the literature could reflect methodological differences in para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…In adolescents, those with good cardiac interoceptive accuracy also appear to recognise others’ facial expressions of sadness and fear better than those with poor interoceptive accuracy ( Georgiou et al, 2018 ). Further, judgements of the intensity of others’ naturalistic disgusted and painful facial expressions have been positively associated with cardiac interoceptive accuracy in a female sample, although accuracy distinguishing these expressions was unrelated to interoceptive accuracy ( Dirupo et al, 2020 ). Increased empathy in those with higher interoceptive awareness may explain why higher interoceptive accuracy has also been found to correlate positively with altruism ( Piech et al, 2017 ).…”
Section: The Relevance Of Interoception To Mental Healthmentioning
confidence: 96%
“…In adolescents, those with good cardiac interoceptive accuracy also appear to recognise others’ facial expressions of sadness and fear better than those with poor interoceptive accuracy ( Georgiou et al, 2018 ). Further, judgements of the intensity of others’ naturalistic disgusted and painful facial expressions have been positively associated with cardiac interoceptive accuracy in a female sample, although accuracy distinguishing these expressions was unrelated to interoceptive accuracy ( Dirupo et al, 2020 ). Increased empathy in those with higher interoceptive awareness may explain why higher interoceptive accuracy has also been found to correlate positively with altruism ( Piech et al, 2017 ).…”
Section: The Relevance Of Interoception To Mental Healthmentioning
confidence: 96%
“…This dimension is typically measured using self-reported questionnaires. The existing interoception literature has mainly focused on interoceptive sensitivity/accuracy, and has highlighted the link between this dimension and several aspects of cognition, including decision making (Werner et al, 2009), representation of interpersonal space (Ferri et al, 2013), and the attribution of affective states from facial expressions (Dirupo et al, 2020).…”
mentioning
confidence: 99%
“…They found that in both study conditions, that is, imagining oneself in a painful situation and imagining a loved one in a painful situation, elicited an enhanced neural response in networks associated with empathy. Moreover, embodied models suggest “that others’ emotional states are processed by re-enacting a representation of the same state in the observer.” ( Dirupo et al, 2020 , p. 16). This, in turn, implies that the degree of accuracy of the understanding of another’s state depends on the accuracy of the perception of one’s own affective states ( Dirupo et al, 2020 ).…”
Section: A History With Many Namesmentioning
confidence: 99%
“…Moreover, embodied models suggest “that others’ emotional states are processed by re-enacting a representation of the same state in the observer.” ( Dirupo et al, 2020 , p. 16). This, in turn, implies that the degree of accuracy of the understanding of another’s state depends on the accuracy of the perception of one’s own affective states ( Dirupo et al, 2020 ). Furthermore, the psychological literature on emotion experience emphasizes that the ability to empathize is facilitated when a person has had similar experiences in the past ( Lambie and Marcel, 2002 ).…”
Section: A History With Many Namesmentioning
confidence: 99%